GeoTracks: adaptive music for everyday journeys - Greenhalgh, Chris; Hazzard, Adrian; McGrath, Sean; Benford, Steve (2016)
Listening to music on the move is an everyday activity for many people. This paper proposes geotracks and geolists, music tracks and playlists of existing music that are aligned and adapted to specific journeys. We describe how everyday walking journeys such as commutes to work and existing popular music tracks can each be analysed, decomposed and then brought together, using musical adaptations including skipping and repeating parts of tracks, dynamically remixing tracks and cross-fades. Using a naturalistic experiment we compared walking while listening to geotracks (dynamically adapted using GPS location information) to walking while listening to a fixed playlist. Overall, participants enjoyed the walk more when listening to the adaptive geotracks. However adapting the lengths of tracks appeared to detract from the experience of the music in some situations and for some participants, revealing trade-offs in achieving fine-grained alignment of music and walking journeys.